2007
DOI: 10.1007/s11664-007-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of ZnO Nanotips Grown on GaN Using Metalorganic Chemical Vapor Deposition

Abstract: ZnO nanotips are grown on epitaxial GaN/c-sapphire templates by metalorganic chemical vapor deposition. X-ray diffraction (XRD) studies indicate that the epitaxial relationship between ZnO nanotips and the GaN layer is (0002)ZnO| |(0002)GaN and (10 " 10)ZnO| |(10 " 10)GaN. Temperature-dependent photoluminescence (PL) spectra have been measured. Sharp free exciton and donor-bound exciton peaks are observed at 4.4 K with photon energies of 3.380 eV, 3.369 eV, and 3.364 eV, confirming high optical quality of ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…At the temperature of 200 K, the free exciton emission dominates the NBE luminescence, whereas the bound exciton emission becomes hardly resolvable, indicating that the decomposition of bound excitons to free ones has almost completed. The quenching temperature of this emission is lower than that for bulk ZnO crystals at 210 K but is higher than that reported by Zhong et al for ZnO nanotips grown on GaN using metalorganic chemical vapor deposition . The transition from the bound exciton emission dominating luminescence to the free exciton dominating one obviously indicates that the dominant room-temperature NBE luminescence results from radiative recombination of free excitons.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…At the temperature of 200 K, the free exciton emission dominates the NBE luminescence, whereas the bound exciton emission becomes hardly resolvable, indicating that the decomposition of bound excitons to free ones has almost completed. The quenching temperature of this emission is lower than that for bulk ZnO crystals at 210 K but is higher than that reported by Zhong et al for ZnO nanotips grown on GaN using metalorganic chemical vapor deposition . The transition from the bound exciton emission dominating luminescence to the free exciton dominating one obviously indicates that the dominant room-temperature NBE luminescence results from radiative recombination of free excitons.…”
Section: Resultsmentioning
confidence: 52%
“…The quenching temperature of this emission is lower than that for bulk ZnO crystals at 210 K 9 but is higher than that reported by Zhong et al for ZnO nanotips grown on GaN using metalorganic chemical vapor deposition. 30 The transition from the bound exciton emission dominating luminescence to the free exciton dominating one obviously indicates that the dominant room-temperature NBE luminescence results from radiative recombination of free excitons.…”
Section: Resultsmentioning
confidence: 99%
“…Lu and co-workers have developed epitaxial Mg x Zn 1 - x O films by alloying ZnO with MgO 6c,6e and observed that it is more resistant to acids. Mg x Zn 1 - x O nanotip films (termed MgZnO−N in this paper) were therefore developed for this work, because they would allow us to employ a wider pH range. The percentage of MgO in alloyed ZnO was varied in the 5−10% range.…”
Section: Resultsmentioning
confidence: 99%
“…The ZnO NBE emission turns out to be dominated by the component related to free excitons above 200 K, as shown in Figures 5 and 6. The evolution of the ZnO NBE emission reveals the decomposition of bound excitons to free ones with the increase of the thermal energy and the release of excitons from donors 26,44 and indicates that the decomposition of bound excitons to free ones has almost completed above 200 K. The temperature-dependent ZnO NBE emission and the…”
Section: Resultsmentioning
confidence: 93%
“…The ZnO NBE emission turns out to be dominated by the component related to free excitons above 200 K, as shown in Figures and . The evolution of the ZnO NBE emission reveals the decomposition of bound excitons to free ones with the increase of the thermal energy and the release of excitons from donors , and indicates that the decomposition of bound excitons to free ones has almost completed above 200 K. The temperature-dependent ZnO NBE emission and the transition from the bound exciton dominating ZnO NBE emission to the free exciton dominating one obviously reveal that the dominant room-temperature ZnO NBE emission results from the radiative recombination of free excitons whether for the bare ZnO NR arrays or for the Ti-covered ZnO NR arrays.…”
Section: Results and Discussionmentioning
confidence: 96%